Determination of Bovine Serum Albumin and Metronidazole by Electrochemical and Fluorescent Methods - Liu, Gen; Wang, Wanjun; Ma, Wei; Sun, Dengming (Asian Journal of Chemistry, 2015)
Poly(L-tyrosine)-graphene modified glassy carbon electrode (PLT-GN/GCE) was prepared by cyclic voltammetric method. Electrochemical method, fluorescence and UV-visible spectroscopy were applied to study the interaction of metronidazole and bovine serum albumin. Fluorescence spectrum of bovine serum albumin in the presence of metronidazole clearly shows that metronidazole acts as a quencher and it is a static quenching process. From the experimental data of electrochemical and fluorescent experiment, the binding constants were deduced to be 5.481 × 104 and 5.369 × 104 L mol-1, respectively and the numbers of binding site were 1.422 and 1.468 at 25 °C, respectively. The calibration plots for bovine serum albumin with electrochemical method and for metronidazole with fluorescent method were in the range of 5 × 10-7 to 1 × 10-4 and 2 × 10-7 to 7 × 10-5 mol L-1, respectively and the detection limits for bovine serum albumin and metronidazole were 1 × 10-7 and 5 × 10-8 mol L-1, respectively. The method had been successfully applied to the determination of metronidazole and bovine serum albumin in samples with satisfactory results.